The plight of the Bangladeshi silk industry: An empirical investigation - Asif Ishtiaque,; Fouzia Haider,; Mahmudul Hasan Rafi,; Mallik Sezan Mahmud,; Md. Helal Uddin,; Ummai Habiba, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
In spite of having a glorious history in the sericulture industry Bangladesh still is not a bright name in silk production and export. Although the agro-climatic situation in Bangladesh greatly favors the development of silk industry, Bangladesh produces very little amount of silk products every year, whereas India, situated beside Bangladesh, is the second largest producer of sericulture. To investigate the reason behind this, a questionnaire survey has been undertaken in which only the owners or managers have been considered as representatives of the industry. A total of 21 silk enterprises was randomly sampled. Data analyses show that almost 57% of the silk enterprises have less than 40 decimal of land while only 19% have more than 100 decimal of land. These enterprises provided very limited facilities for their workers and mostly depended on imported raw materials. Owners pointed out several constraints to the development of silk industry in Bangladesh including insufficient government patronization and recommended several remedial measures including that the Bangladesh Silk Board (BSB) gives out production credit without too much conditions, adoption of modern technology, and information dissemination . It is evident that government, through BSB and BSRTI (Bangladesh Silk Research and Training Institute) has to play a crucial role to pull this industry up from the brink of destruction.